TOURIST PERCEPTION OF ATTRACTIONS, ACCESSIBILITY AND AMENITIES AT THE KARO REGENCY FRUIT AND FLOWER FESTIVAL - Juni Anggraini; Rio Fernandez Tamba; Enty Simanjuntak (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
The Karo Regency Fruit and Flower Festival is an annual event held in Karo Regency. This festival is rooted in local traditions such as thanksgiving for fertile soil and abundant harvests. This study aims to determine tourist perceptions of attractions, accessibility, and amenities at the Fruit and Flower Festival. The method used in this study is descriptive quantitative. In this study, the data source is domestic tourists who have visited the Fruit and Flower Festival one or more times. The number of respondents in this study was 124 respondents. Based on Descriptive Statistical Analysis, tourist perceptions of Attractions, Accessibility, and Amenities at the Karo Regency Fruit and Flower Festival are generally classified as very good, when associated with the range of interpretation of the average score on a Likert scale of 1–5. Attractions and Accessibility received consistent ratings from tourists, indicating that the attractiveness of the festival and ease of access to the location were considered satisfactory and were the main factors in shaping their experience. Meanwhile, tourist perceptions of Amenities were also classified as very good, but showed slightly higher variations, indicating differences in individual experiences regarding comfort, supporting facilities, and additional services during the festival.